WISDOM project – XVIII. Molecular gas distributions and kinematics of three megamaser galaxies - Liang, F-H; Smith, MD; Bureau, M; Gao, F; Davis, TA; Cappellari, M; Elford, JS; Greene, JE; Iguchi, S; Lelli, F; Lu, A; Ruffa, I; et al. (Oxford University Press, 2023)
The co-evolution of galaxies and supermassive black holes (SMBHs) underpins our understanding of galaxy evolution, but different methods to measure SMBH masses have only infrequently been cross-checked. We attempt to identify targets to cross-check two of the most accurate methods, megamaser, and cold molecular gas dynamics. Three promising galaxies are selected from all those with existing megamaser SMBH mass measurements. We present Atacama Large Millimeter/sub-millimeter Array (ALMA) 12CO (2–1) and 230-GHz continuum observations with angular resolutions of ≈0"5. Every galaxy has an extended rotating molecular gas disc and 230-GHz continuum source(s), but all also have irregularities and/or non-axisymmetric features: NGC 1194 is highly inclined and has disturbed and lopsided central 12CO (2–1) emission; NGC 3393 has a nuclear disc with fairly regular but patchy 12CO (2–1) emission with little gas near the kinematic major axis, faint emission in the very centre, and two brighter structures reminiscent of a nuclear ring and/or spiral; NGC 5765B has a strong bar and very bright 12CO (2–1) emission concentrated along two bisymmetric offset dust lanes and two bisymmetric nuclear spiral arms. 12CO (2–1) and 12CO (3–2) observations with the James Clerk Maxwell Telescope are compared with the ALMA observations. Because of the disturbed gas kinematics and the impractically long integration times required for higher angular resolution observations, none of the three galaxies is suitable for a future SMBH mass measurement. None the less, increasing the number of molecular gas observations of megamaser galaxies is valuable, and the ubiquitous disturbances suggest a link between large-scale gas properties and the existence of megamasers.